Organizational Module Design and Architectural Inertia: Evidence from Structural Recombination of Business Divisions - Albert, Daniel (Organization Science, 2018)
The modular organization has been found to be particularly effective in exploring and adapting to changing environments. One powerful means of exploration has been argued to be structural recombination—that is, the splitting and merging of modules. Once undertaken, structural recombination can lead to novel architectural opportunities that enable greater innovation and long-term performance. However, little research exists that explores whether and to what extent a focal module may be readily available for recombinatory opportunities in the first place. In this paper, I investigate the design hierarchy choices related to visibility and information hiding in organizational module designs (i.e., business divisions). In a longitudinal sample of 222 divisions in 18 of the largest European universal banks, I find support for modularity-informed predictions in which visibility and information hiding affect module recombination decisions. In a post hoc analysis, I explore a complementary theoretical explanation of divisions and subunits engaging in political influence. The post hoc results suggest the existence of both a design and a politics component in recombination efforts. I therefore propose that in an organizational context, integrating a political lens into the modularity framework may be of great value in deepening our understanding of how reorganization decisions come about. The online appendices are available at https://doi.org/10.1287/orsc.2018.1210 .